Barão de Marajó: um intelectual e político entre a Amazônia e a Europa (1855-1906) - COELHO, Anna Carolina de Abreu (Universidade Federal do Pará, 2017)
José Coelho da Gama e Abreu, the Baron of the Marajó, graduated in philosophy at the University of Coimbra, became respectable in the Portuguese intellectual circle, even his biographies were published in the press. He belonged to a rich and tradicional Family at Pará whose purchasing power and status were incresead by his marriage to Maria Pombo Brício. The Baron of the Marajó was a man who knew how to stay in power throughout his life performing different public offices during the Republican and Imperial periods. He began his career in 1855 as Director of Public Works in Pará, he was president of the provinces of Pará and Amazonas and congressman; It was a friend of Emperor Pedro II, but that did not stop him to become the first Republican Intendant of the Belém city, personally chosen by the governor Lauro Sodre. He ended his career as state senator in 1906, the year of his death. Popularizer of Amazon's interests in Europe, he was representative of Pará in the Universal Exposition in Paris in 1889 and at the Chicago World Fair in 1893. Despite half a century of public life, the Baron of the Marajó became better known as an intellectual who wrote reference books about Amazon, addressing issues of relevance to the definitions of Brazilian nationality and the specific interests of region his in the works: The Amazon, Amazons Regions and One Protest. His travels, published in From the Amazon to the Seine, Nile, Bosphoro and Danube - Notes of travel, were part of his training, and their reflections on European and Eastern cities have become critical in the performance of different public offices contributing to urban remodeling of the city in the second half of the nineteenth century. From these memories and forgetfulness, we seek to realize the political and intellectual trajectory of the Baron, an emblematic figure to the understanding of national formation in the second half of the nineteenth and early twentieth centuries.